Formation of local spin‐state concentration waves during the relaxation from a photoinduced state in a spin‐crossover polymer. Issue 4 (1st August 2017) - Mariette, Céline; Trzop, Elzbieta; Zerdane, Serhane; Fertey, Pierre; Zhang, Daopeng; Valverde-Muñoz, Francisco J.; Real, José-Antonio; Collet, Eric
Abstract : Broken symmetry and spin‐state concentration waves compete during the relaxation from the photoinduced high‐spin to the ground low‐spin phase of a two‐dimensional spin‐crossover polymer. Abstract : The complex relaxation from the photoinduced high‐spin phase (PIHS) to the low‐spin phase of the bimetallic two‐dimensional coordination spin‐crossover polymer [Fe[(Hg(SCN)3 )2 ](4, 4′‐bipy)2 ] n is reported. During the thermal relaxation, commensurate and incommensurate spin‐state concentration waves (SSCWs) form. However, contrary to the steps forming at thermal equilibrium, associated with long‐range SSCW order, the SSCWs forming during the relaxation from the PIHS phase correspond to short‐range order, revealed by diffuse X‐ray scattering. This is interpreted as resulting from the competition between the two types of SSCW order and another structural symmetry breaking, due to ligand ordering, occurring at low temperature and precluding long‐range SSCW order.